Strategi Pendampingan Komunitas Belajar Dalam Pemanfaatan Platform Merdeka Mengajar Terhadap Implementasi Kurikulum Merdeka - Meuthia, Rira (Universitas Sarjanawiyata Tamansiswa, 2024)
This research aims to explain the strategy for implementing and learning community assisten in the elementary education unit in Kapanewon Sleman in utilizing the Merdeka Mengajar Platform for teachers towards the implementation of the Merdeka Curriculum and describe the impact of the strategy for implementing and assisting the learning community in the elementary education unit in Kapanewon Sleman in utilizing the Merdeka Mengajar Platform for teachers towards the Implementation of the Merdeka Curriculum. This research is a type of qualitative descriptive research. In this study, the research subjects were school principals, teachers, supervisors and students. The data collection techniques used are interviews, observations, and documentation. The data analysis techniques used are data reduction, data presentation and drawing conclusions. And data validity testing is carried out with internal validity, including increasing persistence and triangulation. The results of this research show that there has been an increase in teachers logging into the Merdeka Mengajar Platform. The number of teachers who access independent training ranging from watching videos, post tests, to passing topics by carrying out real actions has also increased. After many teachers logged in to the Merdeka Mengajar Platform and surfed through the learning community, teachers became more active in implementing the independent curriculum. This is proven by the increasing number of teachers who pass independent training topics and take real action.